Control and operation of solid oxide fuel cell distributed generator in a grid-connected power system - Chu, Mingdong. (2009)
Fuel cells are electrochemical devices that convert energy contains in a fuel directly into electricity. The conversion process does not produce by-products that can pollute the environment and has high efficiency. More and more FC generation systems have been developed for clean energy generation purpose. Fuel cell is one form of distributed generation (DG), as it can be integrated in electrical distribution systems. This new form of power generation is foreseen to be a major player in future power systems. Among all DO technologies, Solid Oxide Fuel Cell (SOFC) DC has shown to have high potential for use in existing power systems, in terms with its maintainability, high-efficiency and low emission. This project begins by examining SOFC model developed for power system studies. The intention is to further extend the use of the dynamic model to include the effects of fuel cell parametric changes on system performance. By using Matlab / Simulink, time- domain simulation studies based on the SOFC dynamic system model under varied operating conditions are carried out. In frequency-domain, a linearized SOFC dynamic system model obtained from Taylor’s series is used for analysis through eigen techniques. Sensitivity study of the eigenvalues to parametric changes has also been carried out.